2016
DOI: 10.1080/13562517.2016.1183614
|View full text |Cite
|
Sign up to set email alerts
|

Pulled in many directions: tensions and complexity for academic staff responding to international students

Abstract: This article reports on an interview-based study of the academic practices of staff members in a New Zealand university in response to international students in their classes and under their supervision. International students enter academic cultures which are inevitably different from those which have provided their academic preparation. Participant academics often revealed a tension between trying to support students adjusting to new demands and meeting their own expectations of tertiary teaching. Most had i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Previous small-scale studies have suggested that academic staff are aware of the tension between encouraging their students to become independent learners, and some students' lack of readiness to learn independently. Skyrme and McGee (2016) reported staff finding it difficult to ensure fairness in assessing the work of non-native speakers, and to achieve balance between offering support and assuming autonomy. Anderson, Day and McLaughlin (2006) interviewed 13 experienced Master's dissertation supervisors and found that the dual role of supporting but also developing student agency was a common theme.…”
Section: Research On Pgtmentioning
confidence: 99%
“…Previous small-scale studies have suggested that academic staff are aware of the tension between encouraging their students to become independent learners, and some students' lack of readiness to learn independently. Skyrme and McGee (2016) reported staff finding it difficult to ensure fairness in assessing the work of non-native speakers, and to achieve balance between offering support and assuming autonomy. Anderson, Day and McLaughlin (2006) interviewed 13 experienced Master's dissertation supervisors and found that the dual role of supporting but also developing student agency was a common theme.…”
Section: Research On Pgtmentioning
confidence: 99%
“…Taking up explicitly teaching focused identities can also have a mixed impact on status in research-intensive contexts and can be perceived negatively (Skelton, 2013). More broadly, the developmental possibilities for experienced academic staff will be shaped by their ongoing negotiation of multiple identities and priorities in complex environments characterised by considerable student diversity and a multiplicity of social and material actors (Fenwick et al, 2011;McNaughton and Billot, 2016;Skyrme and McGee, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, when poorly managed, stress, resentment, and misconceptions supplant intercultural understanding amongst agents involved in the internationalization process. Teaching faculty reported challenges associated with modifying their teaching approaches to accommodate international students’ language and cultural needs (Daniels, 2013; Jin & Schneider, 2019; Skyrme & McGee, 2016). Further, faculty felt inadequate in understanding their international students’ backgrounds (Mott-Smith, 2013; Skyrme & McGee, 2016), attributed international students’ challenges to their culture or English (Daniels, 2013; Jin & Schneider, 2019 ), and perceived international students’ learning cultures as incompatible with host institutions’ (Daniels, 2013; Jin & Schneider, 2019; Skyrme & McGee, 2016; Zhao & Bourne, 2011).…”
Section: Chinese International Students As An Analytic Casementioning
confidence: 99%